THE EFFECT OF TAI CHI ON COGNITIVE FUNCTION - SYSTEMATIC REVIEW OF META-ANALYSIS - Mukiyev, Serik (Nazarbayev University School of Medicine, 2024)
Background: Tai Chi shows promise as a target for intervention functions. There are numerous studies about beneficial effect of Tai Chi intervention on cognitive function; however, more systematic research needs to be conducted. Methods: A systematic search up to December 2023 was conducted using PubMed, Google Scholar, and Cochrane. Articles were selected if a meta-analysis of randomized controlled trials was conducted to investigate the effect of Tai Chi therapies on cognitive performance in the general and sick populations. The quality of the included meta-analyses was assessed using AMSTAR 2. Results: This systematic review, based on 21 meta-analyses of 349 included individual RCTs, gives the most thorough overview to date of Tai Chi's usefulness in enhancing cognitive performance in the elderly population. Nonetheless, the results of this study imply that Tai Chi improves cognitive abilities (attention, global cognitive function, visual-spatial ability, cognitive processing speed, and short-term memory). The disparities in research quality and interventions are most likely explained by heterogeneity. Conclusions: This study's findings imply that Tai Chi therapies improve cognitive performance in both the general and ill populations across a wide age range.
Keywords: type of access: gated access